HYGIENE SANITASI PADA BALAI PENGOBATAN PENYAKIT PARU-PARU (BP4) MEDAN PROPINSI SUMATERA UTARA TAHUN 2012 - Jenny Siswi Delima Sipahutar (Lingkungan dan Kesehatan Kerja, 2012)
Sanitation Hygiene InThe Special Hospital Of Lung Treatment At Medan North Sumatera Province in 2012. BP4 Medan is one of the special hospitals of community health service unit owned by the government of North Sumatera for health treatment and special treatment of lung such as tuberculosis. As one special hospital, BP4 Medan should fulfill the criteria of sanitation hygiene including health officers and its environmental. Other parameters determining the quality of the hospital are such as humidity degree, lighting and noisy. Tuberculosis is a malignant disease and can spread for other people caused by any contact with health officers or its environmental based on Health Ministry Rule the Republic of Indonesia of 2004 concerning with sanitation hygiene. The objective of this research was to descript of sanitation hygiene at BP4 Medan especially those health officers and the facilities of health environmental (sanitation) whether it fulfilled health requirement or Health Ministry Rule the Republic of Indonesia of Permenkes No. 1204/2004. The method used was descriptive describing the application of hygiene among health officers and environmental’s facilities at BP4 Medan. The findings showed that not all hygiene of health officers at BP4 Medan fulfilled health requirement in accordance with the principle of sanitation hygiene applied in hospital such as BP4 Medan such as without masker during working, without gloves, talking at working, without washing hand before and after caring the patients, eating and drinking in hospital room. For environmental health which did not fulfill health requirements were such as solid and liquid management, toilet and over capacity bathroom, laundry as well as other intruder animals entering the environmental.In creating good sanitation hygiene and environmental, it is suggested for head of BP4 Medan to improve the facilities of sanitation and give the training related to the principles of sanitation health for health officers at BP4 Medan. Key words : Hygiene, Sanitation, BP4 Medan